ACCUMULATION OF NATURAL ASTAXANTHIN IN HAEMATOCOCCUS PLUVIALIS UNDER STRESS OF SILVER NANOPARTICLES - Lau, Man Tian (2018)
Astaxanthin is a valuable product due to strong antioxidant properties. Astaxanthin have application in various type of industry such as food, medical, and poultry farming. Thus, astaxanthin has a high market demand and should be produced in a larger scale. Haematococcus pluvialis is a species of microalgae that produces the highest level of astaxanthin compared to other species. Thus, H. pluvialis was chosen in this study. Research findings have reported that the growth rate and astaxanthin production of H. pluvialis can be affected by exposure to silver (Ag) nanoparticles, hence this study served to investigate the maximum production rate of astaxanthin by exposing H. pluvialis to different concentrations (10 mg/L, 100 mg/L and 200 mg/L) of silver nanoparticles. The growth rate of H. pluvialis was observed at different concentrations of silver nanoparticles. The growth of H. pluvialis was influenced by silver nanoparticles through the interaction with protein and disruption of ATP synthesis which will then damage the DNA. Maximum astaxanthin production (0.458 ± 0.002 mg/L) was obtained by exposing H. pluvialis to 10 mg/L of Ag nanoparticles on day-14. Ag nanoparticles could inhibit the growth of microorganisms by the generation of free radicals from the surface of silver. To overcome the unfavorable conditions, H. pluvialis produced astaxanthin as protection by stopping the free radical process in the cell. In conclusion, 10 mg/L of Ag nanoparticles was able to induce the highest production of astaxanthin compared to the other concentrations of Ag nanoparticles. Thus, this study demonstrated that the growth rate of H. pluvialis was influenced by different concentrations of Ag nanoparticles and Ag nanoparticles were able to induce the astaxanthin production.